Foreign Aid, Domestic Savings and Economic Growth (Pakistan: 1960 to 1988) (The Pakistan Development Review, 1993)
One of the core tenets of foreign aid theory, particularly as encapsulated in the two-gap model, is that the insertion of foreign resources via free grants, loans, direct investment etc., into a developing economy sets in motion a causal chain of positive influences in the following broad mannerl: aid' ~ increase in investible resources ~ increase in domestic investment ~ more rapid rate of economic growth. Spirited and specific challenges to this approach came from many critics, supported greatly by a number of broad theoreticaF and empirical analyses. For a large part of the latter, the available evidence pointed to a negative relationship between aid and domestic savings. The evidence was largely based on crosssectional data, 'showing that, there was, in addition, reason to suggest a negative relationship between aid and economic growth. 3 The aim of this study is to provide some quantitative evidence on the relationship between foreign aid, domestic savings and economic growth for Pakistan. The analysis is carried out in three parts. Part one contains the methodology and the description of the data. Part two explores the correlation between aid and several other explanatory variables with Pakistan's savings rate, while part three attempts to analyse and explain the regression findings in terms of the effect of aid on economic growth.